Analysis of Economic Growth through Technological Advancement, Investment, Labor and Education - Nur Rifai; Edy Yusuf Agung Gunanto; Joko Hadi Susilo (EKO-REGIONAL, 2021)
This study is aims to determine the variable influence of technological advances, investment, labor and education on economic growth in Central Java Province in 2016-2020, this research is conducted to provide the right economic growth model in accordance with the results of the study. This research is empirical research with quantitative approach. The data used in this study is secondary data from 35 districts/cities in Central Java Province in 2016-2020 so that the number of samples in the study is 175 samples. The data analysis technique in this study uses multiple linear regression analysis with the Fixed Effect model. This study found that the progress variable of technology, labor and education have a significant and positive influence on economic growth in Central Java Province. This study also found the investment variable had an insignificant effect on economic growth in Central Java Province.Keywords: economic growth, technological advancement, investment, labor, education.